The usefulness of ecological concepts: patterns among practitioners - Reiners, Derek S.; Reiners, William A.; Lockwood, Jeffrey A.; Prager, Steven D. (Wiley, 2019)
A survey was distributed to members of the Ecological Society of America in 2014, which asked respondents to rate the usefulness of 131 of the most common, current ecological concepts. As part of the survey, key demographic and professional information was requested from respondents, including age, gender, education level, sector of employment, and primary area (i.e., domain) of interest in ecology. This paper reports how those factors interacted and affected concept ratings. Comprehensive analysis revealed many significant patterns. Among these, we discovered that concept ratings almost invariably increased with age, often dramatically. Also, there was a very strong tendency for males to rate concepts, in general, higher than did females, but the magnitudes of these differences were small. Furthermore, there was a significant gulf between the academic and government employment categories, characterized by academic respondents having rated most concepts higher. This research is important to the ecological community as a quantitative description of the kinds of variation existing among its constituents in terms of types and degrees of concept utility. Self‐knowledge is critical for understanding the discipline and for advancing its educational, research, and environmental initiatives.